PENYELESAIAN SENGKETA PERBANKAN DENGAN MEDIASI - Andika Persada Putera (Universitas Airlangga, 2013)
In principle, the banking industry is a business activity that is fraught with risk (full risk business). However, if managed properly and carefully will result in a huge advantage, otherwise if poorly managed, will lead to greater risk of loss. Therefore, the bank continues to deal with a variety of risks, especially the rapid development of science and technology and the external environment lead bank risk banking business from day to day more and more complex and should be anticipated as possible.